HIV-1 Nef Signaling in Intestinal Mucosa Epithelium Suggests the Existence of an Active Inter-kingdom Crosstalk Mediated by Exosomes - Felli, Cristina; Vincentini, Olimpia; Silano, Marco; Masotti, Andrea (Frontiers in Microbiology, 2017)
The human intestinal mucosal surface represents the first defense against pathogens and regulates the immune response through the combination of epithelial cell functions and immunological factors. Epithelial cells act as sensors of luminal stimuli and interact with the immune cells through signal–transduction pathways, thus representing the first barrier that HIV-1 virus encounters during infection. In particular, the HIV-1 Nef protein plays a crucial role in viral invasion and replication. Nef is expressed early during viral infection and interacts with numerous cellular proteins as a scaffold/adaptor. Nef is localized primarily to cellular membranes and affects several signaling cascades in infected cells modulating the expression of cell surface receptors critical for HIV-1 infection and transmission, also accompanied by the production of specific cytokines and progressive depletion of CD4+ T cells. At the intestinal level, Nef contributes to affect the mucosal barrier by increasing epithelial permeability, that results in the translocation of microbial antigens and consequently in immune system activation. However, the pathological role of Nef in mucosal dysfunction has not been fully elucidated. Interestingly, Nef is secreted also within exosomes and contributes to regulate the intercellular communication exploiting the vesicular trafficking machinery of the host. This can be considered as a potential inter-kingdom communication pathway between virus and humans, where viral Nef contributes to modulate and post-transcriptionally regulate the host gene expression and immune response. In this mini-review we discuss the effects of HIV-1 Nef protein on intestinal epithelium and propose the existence of an inter-kingdom communication process mediated by exosomes.